Gestures In Bts Music Video Blood, Sweet, And Tears:Semiotic Approach - Hadisty Chairani Rawa; Muhammad Kiki Wardana; Misla Geubrina (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study aims to analyze the semiotic meanings and to find out the types of gestures in the BTS Blood, Sweat, and Tears In theory, Roland Barthes discusses three semiotic meanings: denotative, connotative, and myth. This study uses qualitative methods to examine the substance of the meaning of the phenomenon. Researcher used books, theses, journals, and visual images taken from the BTS Blood, Sweat, and Tears music video as data sources to support analysis. The results of this study: there are 10 data where each data has one to four scenes. From the 10 data, there are types of gestures which include 6 data belonging to the illustrator gesture type, 2 data including the embellishment gesture type, and 2 data belonging to the illustrator gesture type. Of all the semiotics presented, the meaning of this music video is the story of resistance, denial, and eventually acceptance. Once cannot stand in the museum of their life forever and look longingly at the mementos of the past. The world is a place of complex relationships between light and dark, good and evil, virtuosity and sin. As we all cross the threshold of puberty we are faced with the choices that shape our lives. No one person is immune to the temptations of such a life and seeing it, understanding it for what it is, and making those choices is all we can do. No one remains untouched by the darkness.